Russia today: The Russian invasion of Ukraine and Russia's public finances - Alfons J. Weichenrieder (Leibniz Institute for Financial Research SAFE, 2022)
This policy letter collects elementary economic statistics and provides a very basic look on Russian public finances (i) to inform the reader's opinion on a possible planning process behind the war against Ukraine and (ii) to discuss prospects of an energy embargo and its capability to affect the stability of the Russian economy.
urn:nbn:de:hebis:30:3-634829
Keywords: 330; Energy Embargo; Invasion; Public Finance; Russia; Ukraine